If the function f is defined as f= 1-2x^3 find the inverse f^-1

Set the function equal to y so y=1-2x^3now rearrange this to set x as the subject 2x^3= 1-yx^3 = (1-y)/2x = ((1-y)/2)^1/3therefore the inverse is f^-1 = ((1-x)/2)^1/3

Answered by Kavita K. Maths tutor

2555 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Given that 9 sin^2y-2 sin y cos y=8 show that (tany - 4)(tany + 2)= 0


Using Pythagoras' theorem, show that sin^2(x)+cos^2(x)=1 for all x.


How do I solve a cubic?


A curve with equation y = f(x) passes through the point (4,25). Given that f'(x) = (3/8)*x^2 - 10x^(-1/2) + 1, find f(x).


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences